Ageing influence in rejuvenated reclaimed asphalt binder incorporating waste cooking oil: A review - Muhammad Ibrahim Khalili, Abd Rahim; Haryati, Yaacob; Siti Nur Naqibah, Kamarudin; Odubela, Christiana Adebola; Norzita, Ngadi; Ekarizan, Shaffie; Putra Jaya, Ramadhansyah; Al-Saffar, Zaid Hazim; Ahmad Shahrir, Amin (IOP Publishing, 2024)
Mixing Recycled Asphalt Binder (RAP) with fresh asphalt mixture offers both environmental and economic advantages. However, the aged asphalt binder in RAP presents a significant challenge in sustainable asphalt pavement construction. One of sustainable approach is by using Waste Cooking Oil (WCO) to bring back the original properties of aged asphalt. Although, WCO ability to soften the aged binder is already established, its ability to improve the binder ability to resist the ageing is remain unknown. Researchers have recently explored the potential of using WCO as a sustainable rejuvenator for RAP, aiming to improve the binder's resistance to ageing. This review covers important topics such the oxidative ageing mechanism in asphalt binders, ageing simulation techniques, the effectiveness of WCO in restoring the RAP properties, and WCO performance to increase asphalt ageing resistance. Through a comprehensive analysis of numerous prior studies, this review sheds light on the impact of WCO on the rheological characteristics, ageing resistance, and mechanical performance of the rejuvenated asphalt binder. The results from the examined literature are that WCO can be utilized as a sustainable rejuvenator in RAP by increase the durability and ageing resistance of binder. This review also points out some of the asphalt binder ageing factors are remains unknown which can be investigate for future research in this field. Ultimately, this review can be referred as a guidance to index and track the ageing factors in rejuvenated RAP by evaluates its characteristics and properties.